Pteruchus (microsporophyll): part 2 of a reassessment of Gondwana Triassic plant genera and a reclassification of some previously attributed. Issue 4 (2nd October 2019) - Anderson, Heidi M.; Barbacka, Maria; Bamford, Marion K.; Holmes, W. B. Keith; Anderson, John M.
Abstract : Anderson, H.M., Barbacka, M., Bamford, M.K., Holmes, W.B.K. & Anderson, J.M., 3 July 2019. Pteruchus (microsporophyll): part 2 of a reassessment of Gondwana Triassic plant genera and a reclassification of some attributed previously. Alcheringa XXX, X–X. ISSN 0311-5518 The microsporophyll genus Pteruchus, belonging to the pteridosperms (seed ferns) in the family Umkomasiaceae (Corystospermaceae), is reassessed comprehensively worldwide and emended. All records are analysed, and some fertile structures previously attributed are reclassified. The Lower Jurassic record of Pteruchus from Germany is ascribed to a new genus as Muelkirchium septentrionalis . Pteruchus is shown to be restricted to the Triassic of Gondwana and is clearly affiliated with the megasporophyll genus Umkomasia and the vegetative leaf genus Dicroidium . It is well represented from Argentina, Antarctica, Australia and southern Africa; the Molteno Formation of southern Africa is by far the most comprehensively sampled, yielding three species and 425 specimens from 22 localities. Nomenclatural problems with the species of Pteruchus are addressed. A key to Pteruchus species is provided; geographic and stratigraphic distributions are tabulated. Heidi M. Anderson [hmsholmes@googlemail.com ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa; Maria Barbacka [mariabarbacka@gmail.com ], W. Szafer Institute of Botany, Polish Academy of Sciences, Lubicz 46, 31-512 Kraków, Poland; Hungarian Natural History Museum, Botanical Department, H-1431 Budapest, Pf. 137, Hungary; Marion K. Bamford [marionbamford@witsacza ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa; W.B. Keith Holmes* [wbkholmes@hotmail.com ], 46 Kurrajong Street, Dorrigo, NSW 2453, Australia; John M. Anderson [jmandersongondwana@googlemail.com ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa. *Also affiliated with: University of New England, Armidale, NSW 2351, Australia.